Serious games and active healthy ageing: a pilot usability testing of existing games. (2016) - Pyae, Aung; Raitoharju, Reetta; Luimula, Mika; Pitkäkangas, Paula; Smed, Jouni
In this paper, we report the findings from the pre-studies of gamified solutions in healthcare (GSH) project, which include mapping the existing games for seniors, conducting a pre-test on console games, interviewing elderly, and a literature review on the motivational factors for elderly. The findings showed us the limitations of the existing games and technologies. The literature review gave the useful game design opportunities. The insights from these pre-studies helped us to form the agenda, activities, and plan for our project. According to the proposed activities, we conducted a pilot testing of existing games with elderly and found out that the existing games have potential to be re-used with further modifications in our project. Furthermore, we learned the important lessons from this testing in terms of game design, interaction, and design opportunities. Then, we continue to re-design the existing games and develop new games followed by a usability testing.